2018
DOI: 10.1175/bams-d-17-0267.1
|View full text |Cite
|
Sign up to set email alerts
|

CESM1(WACCM) Stratospheric Aerosol Geoengineering Large Ensemble Project

Abstract: An overview is presented of the GLENS project, a community-wide effort enabling analyses of global and regional changes from stratospheric aerosol geoengineering in the presence of internal climate variability. CESM1(WACCM) STRATOSPHERIC AEROSOL GEOENGINEERING LARGE ENSEMBLE PROJECTSimone TilmeS, Jadwiga H. RicHTeR, Ben KRaviTz, douglaS g. macmaRTin, micHael J. millS, iSla R. SimpSon, anne S. glanville, JoHn T. FaSullo, adam S. pHillipS, Jean-FRancoiS lamaRque, JoSepH TRiBBia, Jim edwaRdS, SHeRi micKelSon, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
360
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 195 publications
(375 citation statements)
references
References 35 publications
15
360
0
Order By: Relevance
“…The analyses in this study were conducted on three ensembles of simulations, all generated with the 1° horizontal resolution version of CESM1(WACCM) as described by Mills et al (), with the exception of an updated land model, as described by Tilmes et al (). The atmospheric component of this model has 70 vertical layers extending up to 140 km.…”
Section: Simulations and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The analyses in this study were conducted on three ensembles of simulations, all generated with the 1° horizontal resolution version of CESM1(WACCM) as described by Mills et al (), with the exception of an updated land model, as described by Tilmes et al (). The atmospheric component of this model has 70 vertical layers extending up to 140 km.…”
Section: Simulations and Analysismentioning
confidence: 99%
“…Three of those ensemble members were extended out past 2095. In the second ensemble, hereafter called the Geoengineering Large Ensemble (GLENS; Tilmes et al, ), SO 2 was injected at four independent locations: 30°N, 15°N, 15°S, and 30°S (each into a single grid box at 180°E, at the model level ≈5 km above the annual mean tropopause). These locations were chosen because MacMartin et al () found that they are sufficient to meet the chosen objectives of GLENS.…”
Section: Simulations and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The GLENS simulations are described in detail by Tilmes, Richter, Kravitz, et al (). Simulations were conducted with the Community Earth System Model version 1, with the Whole Atmosphere Community Climate Model as its atmospheric component, CESM1(WACCM).…”
Section: Simulationsmentioning
confidence: 99%
“…We estimate the climate response to stratospheric aerosol geoengineering and the resulting detection timescales using simulations from the Geoengineering Large Ensemble Project (GLENS), described by Tilmes, Richter, Kravitz, et al (). These simulations include three features that are important here.…”
Section: Introductionmentioning
confidence: 99%